Neuropsychiatric lupus and infectious triggers (2008)
Infections can act as environmental triggers inducing or promoting systemic lupus erythematosus (SLE) in genetically predisposed individuals. The aim of the present study was to compare the titres of antibodies (Abs) to infectious agents with neuropsychiatric (NPSLE) clinical manifestations. The sera of 260 individuals (120 patients with SLE and 140 geographic controls) were evaluated for the titres of Epstein bar virus (EBV), cytomegalovirus (CMV), toxoplasma, rubella and syphilis Abs using the BioPlex 2200 Multiplexed Immunoassay method (BioRad) and by the ELISA method for Helicobacter pylori and Hepatitis B core Ag. All BioPlex 2200 kits used were in developmental stages. Data analysis was performed using SPSS 9.0 statistical analysis software (SPSS Inc., Chicago, IL, USA, 1999). Correlation analysis indicated that rubella IgM Ab titres were marginally, positively associated with psychosis (P = 0.09). No other associations were detected between the 17 infectious Abs and five NP manifestations. When the positivity cut-off for anti-rubella IgM Abs was set at three standard deviations above normal, three positive subjects were identified: one patient with psychosis and one with depression, for a total NPSLE prevalence of 33.3%. On the contrary, the prevalence of NPSLE in the remaining subjects was 6.5%. Marginally significant correlations between elevated titres of rubella IgM Ab with psychosis and depression were found. Although this nearly 5-fold increase is not statistically significant, it appears that in a larger sample size, significance would be reached. This is the first study reported that examined the correlation of NPSLE manifestations with anti-infectious Abs.